2014
DOI: 10.1227/neu.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation in Craniopharyngiomas

Abstract: Malignant craniopharyngiomas are rare and are associated with a poor prognosis. MTs occur years after the initial benign craniopharyngioma diagnosis and are associated with multiple benign craniopharyngioma recurrence. Results also show that, contrary to widespread belief, there is a poor correlation between radiotherapy and MT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 19 publications
1
21
1
Order By: Relevance
“…Although the exact cause and pathogenesis of such malignant transformation are unknown, previous studies have speculated a likely correlation with radiotherapy. On the other hand, in a review by Sofela AA et al, there was a poor correlation found between malignant transformation and radiotherapy [5]. The present case also showed transformation to malignancy without radiotherapy; thus, we consider that there are other factors contributing to malignant transformation of a craniopharyngioma.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Although the exact cause and pathogenesis of such malignant transformation are unknown, previous studies have speculated a likely correlation with radiotherapy. On the other hand, in a review by Sofela AA et al, there was a poor correlation found between malignant transformation and radiotherapy [5]. The present case also showed transformation to malignancy without radiotherapy; thus, we consider that there are other factors contributing to malignant transformation of a craniopharyngioma.…”
Section: Discussioncontrasting
confidence: 66%
“…The World Health Organization (WHO) classifies a craniopharyngioma as a benign grade 1 tumor known for high recurrence and local aggressiveness despite treatment [5]. However, cases with malignant transformation are extremely rare, with the first presented in 1987, for a total of 28 reported cases, of which only 6 noted a malignant craniopharyngioma without radiotherapy [4,[6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Morphologic criteria of malignancy are not clear. According to the previous literature, at least three of the following features should be present: cellularity and increased nuclear‐cytoplasmic ratio, nuclear pleomorphism and hyperchromatic nuclei, increased mitotic activity or higher Ki67 expression, coagulative necrosis and other histologic features such as solid growth pattern, destruction of basement membrane, infiltrative growth and microvascular proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…37 This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Pearlmentioning
confidence: 99%